1980
DOI: 10.1007/bf01205031
|View full text |Cite
|
Sign up to set email alerts
|

Responses to cell contacts between growth cones, neurites and ganglionic non-neuronal cells

Abstract: The motility of growth cones of embryonic peripheral neurons is not inhibited by contact with the surfaces of neurites or of non-neuronal cells. Rather, growth cones and microspikes adhere to other cell surfaces and often respond with forward movement and elongation in contact with other cells, as they do on adhesive surfaces in vitro. Furthermore, non-neuronal cells do not display contact inhibition when they contact growth cones or neurites. If anything, surface motility and ruffling is stimulated by contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…Interestingly, we have observed this kind of contact inhibition only when growth cones meet neurites from a different neural tissue, while the same behavior is often observed between non-neuronal cells from the same tissue. This pattern is consistent with the observation that contact inhibition does not occur between ciliary growth cones and ciliary net&es, or between DRG growth cones and DRG neurites (Wessells et al, 1980). It has been hypothesized that contact inhibition occurs when a signal is passed between colliding cells.…”
supporting
confidence: 89%
“…Interestingly, we have observed this kind of contact inhibition only when growth cones meet neurites from a different neural tissue, while the same behavior is often observed between non-neuronal cells from the same tissue. This pattern is consistent with the observation that contact inhibition does not occur between ciliary growth cones and ciliary net&es, or between DRG growth cones and DRG neurites (Wessells et al, 1980). It has been hypothesized that contact inhibition occurs when a signal is passed between colliding cells.…”
supporting
confidence: 89%
“…Studies by Aguayo and colleagues (6,8) show that peripheral nerve grafts to the CNS contain a favorable cellular environment for eliciting axonal growth from CNS neurons. At present, several cellular factors are candidates for promoters of axonal growth: (i) surface molecules on non-neuronal cells, Sc, and astrocytes (13,14,32,33); (ii) soluble factors synthesized by supportive cells (glia) or by non-neuronal target cells (11,12,(34)(35)(36); and (iii) ECM molecules including laminin and fibronectin (15)(16)(17)(18)(19)(20)36). Our results indicate that acellular collagen substrates incubated in complete medium do not provide an adequate terrain for rapid axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that filopodia are able to pull on objects (13)(14)(15) and are able to exert forces when they retract (15,16). In the latter two studies, it was estimated that these forces can be as high as several hundreds of piconewtons (pN) (16) or even larger (15).…”
mentioning
confidence: 99%